2017
DOI: 10.1158/0008-5472.can-17-2039
|View full text |Cite
|
Sign up to set email alerts
|

FGF19 Protects Hepatocellular Carcinoma Cells against Endoplasmic Reticulum Stress via Activation of FGFR4–GSK3β–Nrf2 Signaling

Abstract: The tumor microenvironment induces endoplasmic reticulum (ER) stress in tumor cells, an event that can promote progression, but it is unknown how tumor cells adapt to this stress. In this study, we show that the fibroblast growth factor FGF19, a gene frequently amplified in hepatocellular carcinoma (HCC), facilitates a survival response to ER stress. Levels of FGF19 expression were increased in stressed HCC cells in culture and in a mouse xenograft model. Induction of ER stress required the transcription facto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 46 publications
1
65
0
Order By: Relevance
“…Patients with esophageal reflux may be more likely to suffer an increase in FGF19, and all the factors that induced ER stress may facilitate the upregulation of FGF19 and eventually leads to a vicious circle, since increased FGF19, in turn, will promote tumor progression. This is in accordance with results reported that ER acts as a moving organelle with many important cellular functions [33] and FGF19 was reported to protect hepatocellular carcinoma cells against ER stress [12]. Our study established an FGF19-overproducing model to mimic the more malignant phenotype of FGF19-overexpressed LSQ.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patients with esophageal reflux may be more likely to suffer an increase in FGF19, and all the factors that induced ER stress may facilitate the upregulation of FGF19 and eventually leads to a vicious circle, since increased FGF19, in turn, will promote tumor progression. This is in accordance with results reported that ER acts as a moving organelle with many important cellular functions [33] and FGF19 was reported to protect hepatocellular carcinoma cells against ER stress [12]. Our study established an FGF19-overproducing model to mimic the more malignant phenotype of FGF19-overexpressed LSQ.…”
Section: Discussionsupporting
confidence: 92%
“…In patients with hepatocellular carcinoma, high amplification of FGF19 promotes progression and epithelial-mesenchymal transition (EMT) by modulating the GSK3β/β-catenin or STAT3 pathway [8][9][10][11]. FGF19 also protects hepatocellular carcinoma cells against endoplasmic reticulum (ER) stress [12]. Furthermore, FGF19 is critical for the progression of breast cancer [13], prostate cancer [14,15], head and neck squamous cell carcinoma [16] and thyroid cancer [17].…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular ATP levels were determined by ENLITEN ® ATP Assay System (Promega, Madison, MI). Western blot and wound healing assays were carried out as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Western blot and wound healing assays were carried out as previously described. 6,10,[13][14][15] 2.4 | Three-dimensional (3D) tumour spheroid invasion assays 3D invasion assays were performed as we previously described. 16 Briefly, 2 × 10 4 cells were incubated overnight to form 3D spheroid in hanging droplet in a well of an inverted round bottom 96-well plate, followed by adding150 μl mixture of Matrigel: DMEM without serum at the ratio 1:1.…”
Section: Reagents Antibodies and Standard Assaysmentioning
confidence: 99%
“…FGF19/FGFR4 axis recently becomes a promising target for the treatment of HCC. It has been reported that FGF19/FGFR4 inhibited sorafenib-induced ROS generation and apoptosis [69], and was the upstream of NRF2 [70]. But more studies are needed to demonstrate the potential role of FGF19/FGFR4 in NRF2-mediated anti-ferroptosis.…”
Section: Sorafenib-induced Oxidative Stress and Reactive Oxygen Specimentioning
confidence: 99%